Porous polyurethane particles enhanced the acetate production of a hydrogen-mediated microbial electrosynthesis reactor. (June 2022) - Xue, Xiaoyuan; Liu, Zhuangzhuang; Cai, Wenfang; Cui, Kai; Guo, Kun
Abstract: Microbial electrosynthesis (MES) is an electricity-driven microbial CO2 fixation process. It is challenging to achieve high coulombic efficiency (CE) in hydrogen-mediated MES reactors due to the poor hydrogen mass transfer. Here, we report that the addition of porous polyurethane (PU) particles could promote the kL a of H2 by 102%, and thereby enhancing the acetate production rate and CE of a hydrogen-mediated MES reactor by 59% and 11%, respectively. The enhanced performance could be attributed to the promotion of the suspended biomass growth. The maximum acetate production rate (1.48 g·L −1 ·d −1 ) and the acetate titer (17.22 g·L −1 ) achieved in the reactor with PU particles were higher than those of the most reported MES reactors. Microbial community analysis indicated that the impact of PU particles on the bacterial community was negligible. These results demonstrated the addition of PU particles is an efficient way to enhance the performance of hydrogen-mediated MES reactors. Graphical abstract: Unlabelled Image Highlights: Addition of prorous PU particles enhanced the hydrogen mass transfer by 102%. PU particles boosted biomass growth by 72% and acetate production rate by 59%. 1.65 g·L −1 ·d −1 acetate production rate and 17.22 g·L −1 acetate titer were achieved. Porous PU particles are biocompatible and easy to maintain in the reactor.